Peramalan Pendapatan Asli Daerah Kota Samarinda Menggunakan Metode Double Exponential Smoothing Dari Brown - Devira, Annisa Suci; Nasution, Yuki Novia; Suyitno, Suyitno (EKSPONENSIAL, 2023)
Forecasting is a technique for estimating a value in the future by paying attention to past data and current data. One of the forecasting methods for exponentially increasing or decreasing data patterns is Exponential Smoothing. Exponential Smoothing is a method that shows the weighting decreases exponentially with respect to the older observation values. The linear model of the Exponential Smoothing method that uses a two-time smoothing process is Brown's Double Exponential Smoothing method. This study aims to get a forecast of Regional Original Income (PAD) in Samarinda with the double exponential smoothing method. Research data is secondary data from the Samarinda City Regional Revenue Agency (BAPENDA) file. The conclusion of the study is that the results of forecasting PAD in the city of Samarinda in 2021 are IDR 3.374.750.000.000 with an accuracy rate of Mean Absolute Percentage Error (MAPE) of 0,41%.